The germination niche of coastal dune species as related to their occurrence along a sea–inland gradient. (25th May 2020) - Del Vecchio, Silvia; Fantinato, Edy; Roscini, Mauro; Acosta, Alicia T. R.; Bacchetta, Gianluigi; Buffa, Gabriella
Abstract: Aims: The early phases in the life cycle of a plant are the bottleneck for successful species establishment thereby affecting population dynamics and distribution. In coastal environments, the spatial pattern of plant communities (i.e. vegetation zonation) follows the ecological gradient of abiotic stress changing with the distance from the sea. This pattern has been mainly explained based on the adaptation and tolerance to the abiotic stress of adult plants. However, the adult niche may considerably differ from the germination niche of a plant species. The aim of this work was to investigate to what extent abiotic factors (specifically salinity, temperature, nitrogen and their interactions) constrain seed germination along the sea–inland gradient. Location: Latium coast (Central Italy). Methods: Germination tests were performed on seeds of focal species of three different plant communities which establish at increasing distances from the coastline: Cakile maritima subsp . maritima, Elymus farctus, Crucianella maritima . We tested increasing concentrations of NaCl (one of the main abiotic factors which decrease across the sea–inland gradient), and their interactions with temperature and KNO3, to consider other factors which drive germination processes. Results: The tolerance to salinity significantly decreased in relation to the position of species along the coastal zonation. Crucianella maritima was shown to be the least tolerant species, having a decrease in germination >80% across all conditions. KNO3 significantly (although slightly) increased the germination percentage in Cakile maritima subsp . maritima and Elymus farctus . When combined with NaCl, KNO3 alleviated the negative effects of salinity only in Cakile maritima subsp . maritima . Conclusions: The germination responses to the interaction among the tested factors suggest that the germination niche may explain vegetation zonation filtering species at their early stages. Quantifying environmental niches in different phases of the life cycle of plants may provide important insights into community assembly processes. Abstract : We analysed the role of salinity and nutrients, and their interaction with temperature on the germination of focal species of three different plant communities along the sea‐inland gradient. Results suggest that the germination niche contributes to determine species distribution and may explain vegetation zonation by filtering species according to their sensitivity to salt and temperature during germination.